Dynamic Models of Controlled Linear Induction Drives - Rinkevičienė, R.; Petrovas, A. (Elektronika ir Elektrotechnika, 2005)
The article deals with elaborated mathematical model of linear induction motor with Y connected inductor windings. Developed model gives possibility to investigate transients of electric drives with linear induction motors at balanced and unbalanced supply voltage and at equal or distinct parameters of phase windings during motor operation mode, regenerative braking mode and reverse braking mode. Derived formula to calculate developed force is presented. Carried out program to solve the model Calculated results: force developed by linear induction motor, speed, currents of phase windings of inductor and secondary and other parameters are obtained in form of graphs. Graphs show that energy is returned back to motor supply source during regenerative braking. Il.9, bibl. 8 (in English; summaries in Lithuanian, English and Russian).